2021
DOI: 10.1530/ec-21-0344
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum adenosine deaminase levels and Graves’ disease

Abstract: Background: Adenosine deaminase (ADA) is essential for the differentiation and maturation of lymphocytes, while lymphocytes infiltration in thyroid tissue is a vital pathological feature of Graves' disease (GD). The aim of the present study was to compare the concentration of ADA between healthy controls (HC) and patients with GD, and evaluate the association between ADA and GD. Methods: A total of 112 GD patients and 77 matched HC were enrolled in this study. Each participant was examined for thyroid hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The results of the current study indicates that the serum level of adenosine deaminase was higher in AITD than healthy controls. These findings agreed with Lu et al (14) who reported that Patients diagnosed with Graves disease had significantly elevated serum ADA levels compared to healthy controls, and researchers found a strong correlation between elevated serum ADA levels in GD patients and robust thyroid function.Patients with Graves' disease who have untreated hyperthyroidism are at risk for a variety of problems, including but not limited to: diet and exercise, osteoarthritis, thromboembolism, cardiac arrhythmia, bone fracture, vascular dysfunction, and congestive heart disease (15) . Because of an increase in intracellular ATP and oxygen consumption, as well as a dysfunction in the mitochondrial respiratory chain, the hypermetabolic state of hyperthyroidism leads to an imbalance in redox balance and an increase in peripheral tissue reactive oxide species (ROS) generation (16) .…”
Section: Discussionsupporting
confidence: 92%
“…The results of the current study indicates that the serum level of adenosine deaminase was higher in AITD than healthy controls. These findings agreed with Lu et al (14) who reported that Patients diagnosed with Graves disease had significantly elevated serum ADA levels compared to healthy controls, and researchers found a strong correlation between elevated serum ADA levels in GD patients and robust thyroid function.Patients with Graves' disease who have untreated hyperthyroidism are at risk for a variety of problems, including but not limited to: diet and exercise, osteoarthritis, thromboembolism, cardiac arrhythmia, bone fracture, vascular dysfunction, and congestive heart disease (15) . Because of an increase in intracellular ATP and oxygen consumption, as well as a dysfunction in the mitochondrial respiratory chain, the hypermetabolic state of hyperthyroidism leads to an imbalance in redox balance and an increase in peripheral tissue reactive oxide species (ROS) generation (16) .…”
Section: Discussionsupporting
confidence: 92%
“…In addition to its enzymatic property, ADA is also a costimulatory molecule that is engaged in a variety of cellular processes, such as regulation of DNA synthesis, mediation of adenosine receptor signaling and modulation of intercellular interactions ( 12 ). Increased serum ADA activity has been shown to be involved in various metabolic and inflammatory diseases, including atherosclerosis ( 13 ), thrombosis ( 14 ), acute myocardial infarction ( 15 ), hypertension ( 16 , 17 ), Graves’ disease ( 18 ), and T2D ( 19 ). Metabolic abnormalities and inflammatory disorders are essential conditions for DPN in T2D ( 20 ).…”
Section: Introductionmentioning
confidence: 99%